Lipoprotein Lipase Expression in Hypothalamus Is Involved in the Central Regulation of Thermogenesis and the Response to Cold Exposure - Laperrousaz, Elise; Denis, Raphaël G.; Kassis, Nadim; Contreras, Cristina; López, Miguel; Luquet, Serge; Cruciani-Guglielmacci, Céline; Magnan, Christophe (Frontiers in Endocrinology, 2018)
Lipoprotein lipase (LPL) is expressed in different areas of the brain, including the hypothalamus, and plays an important role in neural control of the energy balance, including feeding behavior and metabolic fluxes. This study tested the hypothesis that hypothalamic LPL participates in the control of body temperature. We first showed that cold exposure induces decreased activity and expression of LPL in the mouse hypothalamus. We then selectively deleted LPL in the mediobasal hypothalamus (MBH) through an adeno-associated virus approach in LPL-floxed mice, and generated MBHΔLpl mice with 30-35% decrease in hypothalamic LPL activity. Results showed a decrease in body temperature in MBHΔLpl mice as compared to controls at 22°C. Exposure to cold (4°C for 4h) decreased the body temperature of the control mice while that of the MBHΔLpl mice remained similar to that observed at 22°C. MBHΔLpl mice also showed increased energy expenditure during cold exposure, when compared to controls. Finally, the selective MBH deletion of LPL also increased the expression of the thermogenic PRMD16 and Dio2 in subcutaneous and perigonadal adipose tissues. Thus, the MBH LPL deletion seems to favor thermogenesis. This data demonstrates that for the first time hypothalamic LPL appears to function as a regulator of body temperature and cold-induced thermogenesis.